Analisis kesenjangan tabungan dan investasi domestik di kawasan ASEAN - Marselina, Eli; Tan, Syamsurijal; Amril, Amril (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
This study aims to analyze the development of the domestic savings and investment gap in the ASEAN region as well as to analyze the factors that influence the domestic savings and investment gap in the ASEAN region for the 2010-2020 period. This study uses linear regression with panel data regression analysis. The results of the study show that (1) simultaneously there is a significant relationship between the independent variables of economic growth, inflation rate, total population and foreign direct investment on the gap between domestic savings and investment in the ASEAN region, (2) partially inflation rate and population size have an effect on on the gap between domestic savings and investment in the ASEAN region, (3) partially economic growth and foreign direct investment have no effect on the gap between domestic savings and investment in the ASEAN region.